Amla (Emblica officinalis) alleviates doxorubicin-induced cardiotoxicity and nephrotoxicity in rats - Mandeep Kumar Arora; Mary Singh; Ritu Tomar; Lakhveer Singh; Ashok Jangra (Elsevier, 2024)
Introduction: Doxorubicin (DOX) is a widely used anticancer drug known for its significant cardiotoxic and nephrotoxic effects. Seeking remedies to mitigate these adverse effects is crucial. This study investigates the potential of Emblica officinalis (Amla) extract, a prominent component in Chinese and Indian traditional medicine systems, in alleviating DOX-induced cardiotoxicity and nephrotoxicity. Methods: DOX (20 mg/kg i.p., once) was given to rats to cause acute cardiotoxicity and nephrotoxicity. Rats received 16 similar and cumulative doses of DOX (1.25 mg/kg, i.p.) on alternate days for chronic cardiotoxicity and nephrotoxicity. Biochemical and histological evaluations were done to confirm the onset of cardiotoxicity and nephrotoxicity. Results: The cardioprotective and nephroprotective effects of Amla extract (AE) (150 mg/kg p.o. and 300 mg/kg p.o) were evaluated in comparison to Vitamin E (25 mg/kg p.o.). The treatment with AE (300 mg/kg/day, p.o.) considerably prevented DOX-induced cardiotoxicity, nephrotoxicity, and oxidative stress by positively altering the integrity of glomeruli, restoring the tissue GSH and decreasing serum TBARS. AE (300 mg/kg) was found to be more cardioprotective and nephroprotective than Vitamin E (25 mg/kg p.o.). Discussion: It may be concluded that the induction of cardiotoxicity and nephrotoxicity in rats may be due to DOX-induced oxidative stress, and chronic treatment with AE (300 mg/kg) is an effective way to alleviate the cardiotoxic and nephrotoxic adverse effects of DOX in rats. Moreover, given Amla's historical and contemporary significance in Chinese and Indian traditional medicine systems, its potential therapeutic role merits further exploration in clinical settings.